Factors affecting speed of industrialized building system (IBS) projects in Malaysia - Alaghbari, Wa’el; A. , Salim; M. R. , Abdul Kadir; A. , Asonway (2008)
This study attempts to identify the factors affect the speed of IBS and the probability level to select either IBS or conventional method. A questionnaire was distributed in order to collect the data. It consists of 6 main factors namely: high productivity of structural elements, using of moulds, using of new equipments and technology, workers skills and experience, equipments and mechanical plants used, and the materials used. The level of importance of the categories was measured and ranked in terms of relative importance weights. Logit linear analysis was used to choose either using IBS or Non- IBS (conventional system) in term of speed. In addition, it was used to test and compare the affecting of different speed factors on the probability to choose the construction methods. The finding of this study was found that the high productivity of structural elements is the main factor. Using of moulds factor, and using of new techniques and technology factor were the second important factors affecting the speed of industrialized building system in construction projects in Malaysia. This paper suggests possible improvements that could be made in order to reduce the delays and increase the productivity in the construction building industry.